Estudo químico de Spiranthera odoratissima e atividades biológicas em formigueiros de Atta sexdens rubropilosa - Terezan, Ana Paula (Universidade Federal de São Carlos, 2007)
This work describes the biossay-guided the phytochemical study of Spiranthera odoratissima (RUTACEAE), with test against the symbiotic fungus Leucoagaricus gongylophorus, leaf-cutting ant Atta sexdens rubropilosa and pectinases enzymes of the faecal fluid of leaf-cutting ant. The phytochemical study of actives extracts allowed the identification of 15 substances: lupeol, lupenone, sitosterol, estigmasterol, campesterol, dictamine, ã-fagarine, esquimianine, 4,8-dimetoxyfuro[2,3-B]quinoline-5-7-diol, 1-methyl-2-phenyl-4- quinolone, 1-methyl-8-methoxy-2-phenyl-quinolin-4-one, limonine, limonexic acid, iso-limonexic acid e 23-hidroxy-21-oxo-dihydroodoratine. The compounds 1-methyl-8-methoxy-2-phenyl-quinolin-4-one, iso-limonexic acid e 23-hidroxy- 21-oxo-dihydroodoratine are described for the first time in the literature. 4,8- Dimetoxyfuro[2,3-B]quinoline-5-7-diol, 1-methyl-2-phenyl-4-quinolone, limonine and limonexic acid were isolated for first time from the Spiranthera genus. The branch extracts of the S. odoratissima were active against the L. gongylophorus fungus , inhibiting 100% of its growth and showed insecticide activity against leaf-cutting ants in survival biossay, with significant reduction leaf-cutting ants lifetime (5,5 days) when compared with the control group (25 days). The antimicrobial tests showed low activity of S. odoratissima against the The flavone biotransformation studies carried out with the symbiotic fungus L. gongylophorus on YNB liquid medium, solid medium and on the ants nest of the A. sexdens rubropilosa showed degradation of flavone. This degradation probably is done by the enzymatic system of the symbiotic fungus L. gongylophorus and others microorganisms presents on waste of ants nest.
Phytochemical study of Spiranthera odoratissima and biological activity in ants nest of Atta sexdens rubropilosa
Keywords: Atividade inseticida; Spiranthera odoratissima; Atta sexdens rubropilosa; Leucoagaricus gongylophorus; CIENCIAS EXATAS E DA TERRA::QUIMICA